2013
DOI: 10.1371/journal.pone.0075121
|View full text |Cite
|
Sign up to set email alerts
|

The Mitochondrial Genome Impacts Respiration but Not Fermentation in Interspecific Saccharomyces Hybrids

Abstract: In eukaryotes, mitochondrial DNA (mtDNA) has high rate of nucleotide substitution leading to different mitochondrial haplotypes called mitotypes. However, the impact of mitochondrial genetic variant on phenotypic variation has been poorly considered in microorganisms because mtDNA encodes very few genes compared to nuclear DNA, and also because mitochondrial inheritance is not uniparental. Here we propose original material to unravel mitotype impact on phenotype: we produced interspecific hybrids between S. ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
62
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(69 citation statements)
references
References 86 publications
7
62
0
Order By: Relevance
“…Albertin et al [50] and Solieri et al [51] both produced interspecific hybrids between S . cerevisiae and S .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Albertin et al [50] and Solieri et al [51] both produced interspecific hybrids between S . cerevisiae and S .…”
Section: Discussionmentioning
confidence: 99%
“…However, we showed that, for each crossing, there are still hybrids progeny with mtDNA types from both parents after a given number of generations. In Albertin et al [50] and Solieri et al [51], hybrids per cross were recurrent cultured on YPD-agar plates from one colony to a given number of generations. These populations underwent severe bottlenecks during subculturing.…”
Section: Discussionmentioning
confidence: 99%
“…Yeast Strains-Four diploid S. uvarum strains, seven diploid S. cerevisiae strains, and their 55 hybrids produced from a half diallel design (53) were analyzed in this study. Parental strains were derived from strains isolated from different geographical locations and from either natural or food-processing origins (Table I): the S. cerevisiae strains were isolated from diverse media (distillery, enology, oak exudate) to maximize the genetic diversity within this species (54); the S. uvarum strains, originating from grape must or cider fermentation, were chosen to cover a wide part of the genetic diversity of the S. uvarum species (Masneuf-Pomarè de, I., personal communication).…”
Section: Methodsmentioning
confidence: 99%
“…Construction of the Half Diallel Design-Hybrid construction was performed as described in Albertin et al (53). Briefly, the 11 diploid parental strains were transformed with a cassette containing the HO allele disrupted by a gene of resistance to either G418 (ho::KanR), hygromycin B (ho::HygR), or nourseothricin (ho::NatR).…”
Section: Methodsmentioning
confidence: 99%
“…) and has a strong impact on growth and respiration rates under aerobic conditions (Albertin et al . ). In contrast, these hybrids displayed similar performance during the fermentation of synthetic grape juice.…”
Section: Introductionmentioning
confidence: 97%